The Role of Muhammad Iqbal in Islamic Thought - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Universitas Islam Negeri Raden Intan Lampung, 2024)
Abstract;Since the middle of 19th century, Muslims have made their ways to variously response to the ideas of modernity, many of which were markedly inspired by the pan-Islamist activist, Jamal al-Din al-Afghani, who started to espouse modern aspiration and inaugurate the Islamic reform movement throughout the Muslim world. This paper highlights the role of Muhammad Iqbal (1879-1938) in Islamic thought, through his philosophical premises to awaken the new Islamic consciousness in the Indian subcontinent, in continuing the tradition of al-Afghani and his religious struggle. The study was qualitative in nature designed based on documentary survey and analysis. It reviews related materials from normative and inductive perspectives. The data were analysed using scientific, descriptive, analytical and historical approaches to reach the final conclusion. The finding shows that Iqbal had formulated unprecedented ideas toward reconstruction and modernization in political, economic and social aspect. His works manifested broad and cohesive philosophical arguments and influences that largely impacted Muslim thought which help to develop their rational and dynamic framework to reconstruct the significance dimension of ijtihad and renewed their profound spiritual and metaphysical consciousness of the perennial and transcendental values of religion and its relevance to the modern context.Keywords:Applied Islamology; Arkoun; Episteme; Socio-Humanities Applications. Abstrak;Sejak pertengahan abad ke-19, umat Islam telah memberikan berbagai bentuk respon terhadap kemodenan, yang banyak diilhamkan dari pemikiran Sayyid Jamal al-Din al-Afghani, pencetus idea pan-Islam. Artikel ini menyorot peranan Muhammad Iqbal (1879-1938) ahli falsafah dan pujangga Islam dari Selatan India dalam melanjutkan perjuangan al-Afghani dalam membangkitkan kefahaman baru Islam yang progresif. Premis falsafah yang dibangunkan dalam karya-karyanya memperlihatkan idea-idea pembaharuan yang mendalam tentang aspek-aspek perubahan dan pemodenan dalam konstruk politik, ekonomi dan sosial. Kajian ini dirangka berasaskan metode normatif dan induktif dari jenis penelitian kualitatif. Ia menerapkan metode dokumentasi historis dan analisis dalam peninjauan bahan yang kemudiannya dianalisis secara saintifik, analitis, dan deskriptif bagi mendapatkan rumusan dan kesimpulan akhir. Penemuan mendapati bahawa Iqbal telah melontarkan ide-ide pembaharuan dan rekonstruksi dalam karyanya The Reconstruction of Religious Thought in Islam berasaskan pertimbangan-pertimbangan falsafah yang rasional dan dinamik dalam rangka membangun kembali alam fikiran Islam dan memulihkan struktur hukum, moral dan budayanya. Ia menunjukkan pengaruh yang meluas dari karyanya yang memberi impak yang mendalam terhadap upaya pembaharuan dan pengembangan ijtihad dan kesedaran metafizik yang transenden dan perenial.Kata Kunci: Aplikasi Ilmu Sosial-Humaniora; Arkoun; Episteme; Islamologi Terapan.